The effect of molybdenum on interphase precipitation and microstructures in microalloyed steels containing titanium and vanadium. (December 2018) - Gong, P.; Liu, X.G.; Rijkenberg, A.; Rainforth, W.M.
Abstract: Despite much research into steels strengthened through interphase precitation, there remains much that is not clear, such as the role of a range of elements, particularly Mo, in the interphase precipitation process. Four steels were manufactured with identical composition, but with variations in Ti, V, Mo and N content to investigate the effect of composition on interphase precipitation. Alloys were rapidly cooled from the single austenite phase field and isothermally transformed at 630 °C and 650 °C for 90min. The addition of Mo was found to significantly reduce the austenite to ferrite transformation kinetics, particularly for the V steel. Interphase precipitation was observed in all alloys at both transformation temperatures. For the Ti bearing steel, the two types of precipitate were observed throughout the sample, namely TiC (finer) and Ti2 C (coarser), while for the V bearing steels, VC (finer) and V4 C3 (coarser) were observed. Where Mo was present in the alloy, it was found dissolved in all carbide types. The (Ti, Mo)C and (V, Mo)C formed by classical planer interphase precipitation (PIP) while the (Ti, Mo)2 C and (V, Mo)4 C3, that had a much wider row spacing, formed through curved interphase precipitation (CIP). Each adopted one variant of the Baker-Nutting orientation relationship. The Ti-microalloyed steels exhibited the smallest precipitates of all the steels, which were approximately the same size irrespective of whether Mo was present in the alloy and irrespective of the transformation temperature. However, the addition of Mo to the V bearing steels resulted in a significant increase in precipitate volume fraction and a reduction in precipitate size. The mechanisms of interphase precipitation leading to the coincident production of two different precipitate types is considered and the role of Mo on the interphase precipitation process is discussed. The resultant effect on strength is considered. Graphical abstract: Image 1